Low Insulin-like Growth Factor-II Levels Predict Weight Gain in Normal Weight Subjects with Type 2 Diabetes - Heald, Adrian H.; Kärvestedt, Lars; Anderson, Simon G.; McLaughlin, Julie; Knowles, Anne; Wong, Louise; Grill, Valdemar; Cruickshank, J. Kennedy; White, Anne; Gibson, J. Martin; Brismar, Kerstin (The American journal of medicine, 2006)
Insulin-like growth factor (IGF)-I and IGF-II are important in the regulation of metabolism and growth. We previously reported in normoglycemic individuals of normal weight that low circulating IGF-II predicts future weight gain. We subsequently investigated whether such relationships persisted in circumstances of type 2 diabetes. In 224 subjects with type 2 diabetes we assessed the association between baseline IGF-II levels and risk of weight gain (>2.0 kg) at the 5-year follow-up. At follow-up, 90 participants (40.2%) gained more than 2.0 kg in body weight. For subjects (body mass index <26) at baseline, mean IGF-II levels were significantly lower in those who gained more than 2 kg in weight than in subjects of stable weight, 454 ng/mL (95% confidence interval 349-559) versus 620 ng/mL (534-705) (F = 7.4, P = .01). For this subgroup low circulating IGF-II at baseline strongly correlated with weight gain (Spearman rho = −0.52, P <.001). With increasing weight, the relationship no longer prevailed. Logistic regression showed that for body mass index less than 26, individuals at baseline for each 100 ng/mL increase in baseline IGF-II there was a 47% decreased risk of gaining 2.0 kg or more in weight. Adjustment for treatment group did not materially alter this relationship. There was no difference in baseline IGF-II by treatment group. There was no difference between the group with weight gain and the group with stable weight in those who additionally received insulin or sulfonylurea treatment in the 5 years between the baseline visit and the follow-up. In subjects of normal weight with type 2 diabetes, baseline IGF-II concentration is inversely related to future weight gain, independent of treatment effect, strengthening the putative role for IGF-II in regulating fat mass. We propose that IGF-II measurement has potential utility in this group for targeting such individuals for early intervention.